2002
DOI: 10.1364/ao.41.004108
|View full text |Cite
|
Sign up to set email alerts
|

Pattern recognition with a digital holographic microscope working in partially coherent illumination

Abstract: We describe the implementation of the automatic spatial-frequency-selection filter for recognition of patterns obtained with a digital holographic microscope working with a partially coherent source. The microscope provides the complex-optical-amplitude field that allows a refocusing plane-by-plane of the sample under investigation by numerical computation of the optical propagation. By inserting a correlation filter in the propagation equation, the correlation between the filter and the propagated optical fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…5 shows the unwrapped phase contrast image. The quantitative value of the phase is converted to a length scale using equation (12). It can be directly used for 3D profile measurement of the laser mark.…”
Section: (A) Reconstructed Amplitude Contrast Image (B) Phase Contrasmentioning
confidence: 99%
See 1 more Smart Citation
“…5 shows the unwrapped phase contrast image. The quantitative value of the phase is converted to a length scale using equation (12). It can be directly used for 3D profile measurement of the laser mark.…”
Section: (A) Reconstructed Amplitude Contrast Image (B) Phase Contrasmentioning
confidence: 99%
“…Various digital approaches have been presented to correct the curvature of the MO by using a digital phase mask [7][8][9]. It has been demonstrated that quantitative phase contrast images are possible and can be used directly for applications in optical metrology [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…DHM provides a numerical investigation of the third dimension by performing a plane-by-plane refocusing that overcomes the small depths of focus due to the high numerical apertures of the microscope lenses and the high magnification ratios. Due to the knowledge of the full complex amplitude provided by DHM, advanced hologram processing techniques were successfully developed, as for few examples, for automated pattern recognition [14,15], the control of the parameters and aberrations of DHM [16,17] and automated refocusing [18][19][20][21][22]. To counter the coherent noise, several configurations were proposed with optical sources of partial coherence [2,12,13,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…In Digital Holography (DH) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15], direct recording of a hologram by means of a solid-state sensor is possible in alternative to the use of film or plate. The recorded digital hologram can be numerically processed to calculate the complex wave front originally scattered or diffusively transmitted by the object under investigation.…”
Section: Introductionmentioning
confidence: 99%
“…From the complex wave front it is possible to extract separately the amplitude and the phase. Numerous applications have been exploited in the recent years for the DH in various contexts like image encryption [2], 3D imaging and object comparison [3], metrology for mechanics of materials [4] recognition of three-dimensional objects and patterns [5][6], and microscopy [7]. One of the advantages offered by DH is the possibility to use multiple wavelengths.…”
Section: Introductionmentioning
confidence: 99%